Basalt Geochemistry and Mantle Flow During Early Backarc Basin Evolution: Havre Trough and Kermadec Arc, Southwest Pacific. (24th February 2021) - Gill, J.; Hoernle, K.; Todd, E.; Hauff, F.; Werner, R.; Timm, C.; Garbe‐Schönberg, D.; Gutjahr, M.
Abstract: The Havre Trough (HT) backarc basin in the southwest Pacific is in the rifting stage of development. We distinguish five types of basalt there based on their amount and kind of slab component: backarc basalts (BAB) with little or no slab component, modified BAB with slight amounts, reararc (RA) with more, remnants of the preexisting arc (Colville Ridge horsts), and arc front volcanoes within the HT. Previous subarc mantle is quickly removed and replaced by more fertile mantle with less slab component. The ambient mantle is "Pacific" isotopically, and more enriched in Nb/Yb and Nd and Hf isotope ratios north of the Central Kermadec Discontinuity at 32°S than to the south. The contrast may reflect inheritance in the south of mantle that was depleted during spreading that formed the southern South Fiji Basin and a higher degree of melting because of a wetter slab‐derived flux. The slab component also differs along strike, more like a dry melt in the north and a supercritical fluid in the south. The mass fraction of slab component increases southward in the backarc as well as the arc front. RA volcanoes have the most slab component (1%–2%) and form indistinct ridges at high angles to, and <50 km behind, frontal volcanoes. Backarc basalts have less and occur throughout the basin. Slab components are distributed further into the backarc, and more irregularly, during the rifting than spreading stage of backarc basin development. The rifting stage is disorganized geochemically as well as spatially. Plain Language Summary: Island arcs split as do continents, with new ocean crust forming between the rifted parts. Splitting progresses from early rifting to mature spreading stages. We present the most thorough geochemical data yet for volcanic rocks erupted during the rifting stage of one of these events. We found that they are derived from new mantle that flowed quickly into the system to replace what fed the arc. The new mantle is more inherently fertile but has fewer additions from the subducting slab than what fed the arc. Both the mantle and slab components differ north versus south of a major tectonic boundary within the basin at 32°S. The slab components are similar during both the rifting stage in the Havre Trough and spreading stage elsewhere, but are distributed or tapped differently, being more irregular during rifting. Rifting leaves permanent geochemical records that modulate the geochemical evolution of arc crust that can be added to continents. Key Points: The Havre Trough is now one of the most thoroughly analyzed backarc basins Mantle beneath a backarc basin is replaced quickly even during the rifting stage before spreading starts Slab components during the rifting stage are similar to those during spreading but are more disorganized during rifting